Chapter Префиксация глаголов неопределенного движения в русском языке - Ruvoletto, Luisa (Biblioteca di Studi Slavistici, 2017)
This paper deals with the different meanings and functions of prefixes in perfective verbs derived from the indeterminate motion verbs chodit', nosit' and ezdit'. In some expressions with transitive verbs (e. g. vychodit', donosit' and naezdit') the prefixes are lexical. Their function consists in creating accomplishment verbs with a resultative meaning. On the other side, the prefixes po-, za- and ot- in such verbs as pochodit', zachodit', ot''ezdit' are superlexical. They have the function of expressing additional meanings which refer to the duration, inception and cessation of the action.